2011
DOI: 10.2134/agronj2010.0471
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fertilization on Maize under Different Production Practices in the North China Plain

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. A gricultural intensification through the use of high-yielding crop cultivars, chemical fertilizers and pesticides, irrigation, and mechanization has been responsible for dramatic increases in grain production in developing countries during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 20 publications
4
22
0
3
Order By: Relevance
“…5). This result, consistent with recent field experiments (Niu et al 2011, Tan et al 2012, Wu et al 2013, underscores the importance of these nutrients for enhancing production. Increases in phosphorus and potassium levels are attributable to 6.6% and 11.6% increases, respectively, in quantities applied per unit area (Fig.…”
Section: Decomposition Of Effects On Yieldsupporting
confidence: 91%
“…5). This result, consistent with recent field experiments (Niu et al 2011, Tan et al 2012, Wu et al 2013, underscores the importance of these nutrients for enhancing production. Increases in phosphorus and potassium levels are attributable to 6.6% and 11.6% increases, respectively, in quantities applied per unit area (Fig.…”
Section: Decomposition Of Effects On Yieldsupporting
confidence: 91%
“…The partial K balance (PKB), calculated by taking the ratio of K nutrient removal in aboveground to fertilizer K application rate, was over 1.0 for both cash and grain crops (Fig. 6), showing that K removal by crop uptake was more than K input from K fertilizer application, which was supported by many other studies (Liao et al, 2008;Niu et al, 2011;Tan et al, 2012;Zhang et al, 2011). The PKB was higher with 2.1 (ranging from 1.1 to 4.2) for cash crop than that of 1.3 (ranging from 1.0 to 1.5) for grain crops (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the increased use of K fertilizer continues to be required on soils planted to grain crops since soil K level for grain crops was below the critical levels and no increase in soil indigenous K supply was observed. These results can be supported by relative yield and a great number of site-to-site reports as well (Yu et al, 2009;Tan et al, 2007Tan et al, , 2010Tan et al, , 2012Zhou, 1999, 2012;Niu et al, 2011). Although with the development of agricultural mechanization and more crop residue being returned back to soils, reports indicated that straw return alone is not sufficient to maintain the soil K balance (Tan et al, 2007(Tan et al, , 2012Wang et al, 2010) and chemical K fertilizer application is essential to maintain both high yield and soil K balance (Xing et al, 2007(Xing et al, , 2010.…”
Section: Discussionsupporting
confidence: 52%
“…K is an important element which plays major role in translocation of different ions in plant part from soil which leads to improvement in various nutrient use efficiencies (Niu et al, 2011). It is concluded that the study showed integrated application of K brought significant improvement in yield of both maize and wheat crops in a cropping cycle compared to sole source of K application.…”
Section: Nutrients Use Efficiencymentioning
confidence: 87%